To solve the system of equations using the substitution method, we have the following equations:
- \( 2x + 2y = 6 \) (Equation 1)
- \( 3x + 2y = 9 \) (Equation 2)
Step 1: Solve one of the equations for one variable. Let’s solve Equation 1 for \( y \).
Starting with Equation 1: \[ 2x + 2y = 6 \]
Subtract \( 2x \) from both sides: \[ 2y = 6 - 2x \]
Now, divide by 2: \[ y = 3 - x \quad \text{(Equation 3)} \]
Step 2: Substitute Equation 3 into Equation 2.
Now substitute \( y = 3 - x \) into Equation 2: \[ 3x + 2(3 - x) = 9 \]
Distributing \( 2 \): \[ 3x + 6 - 2x = 9 \]
Combine like terms: \[ x + 6 = 9 \]
Subtract \( 6 \) from both sides: \[ x = 3 \]
Step 3: Substitute \( x \) back into Equation 3 to find \( y \).
Now substitute \( x = 3 \) into Equation 3: \[ y = 3 - 3 \] \[ y = 0 \]
So the solution to the system of equations is: \[ (x, y) = (3, 0) \]
Thus, the answer is \( (3, 0) \).